Cardiac surgery for patients aged 65 years and older: a long term survival analysis. Issue 6 (December 1988) - Livesey, S; Caine, N; Spiegelhalter, D J; English, T A; Wallwork, J
Abstract : Between January 1973 and December 1984, 562 patients aged greater than or equal to 65 had cardiac surgery at Papworth Hospital. Most had mitral or aortic valve replacements (coronary artery bypass grafting was not introduced for this age group at Papworth until 1977). The overall operative mortality, defined as death within thirty days or death before leaving hospital, was 7.3%. There were no early deaths in patients undergoing coronary artery bypass grafting surgery. Questionnaires sent to general practitioners in East Anglia traced 86.0% of the patients who survived to leave hospital. The longer term survival rates for all patients were 88.0%. (95% confidence interval (CI) 85 to 91) at one year and 74.4% (95% CI 69 to 79) at five years. The rates for those patients who survived the initial few months were 96.3% (95% CI 94 to 98) at one year and 81.5% (95% CI 77 to 86) at five years and these rates were no different from those in the general population aged greater than or equal to 65.